2021
DOI: 10.48550/arxiv.2111.01158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Satellite mass functions and the faint end of the galaxy mass-halo mass relation in LCDM

Abstract: The abundance of the faintest galaxies provides insight into the nature of dark matter and the process of dwarf galaxy formation. In the LCDM scenario, low mass halos are so numerous that the efficiency of dwarf formation must decline sharply with decreasing halo mass in order to accommodate the relative scarcity of observed dwarfs and satellites in the Local Group. The nature of this decline contains important clues to the mechanisms regulating the onset of galaxy formation in the faintest systems. We explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In parallel, semi-analytic and empirical galaxy-halo connection models have been combined with observations to infer ultra-faints' halo properties; in these models, the number of observable ultra-faints suggests that these systems occupy halos with masses down to ∼ 10 8 M (near the "atomic cooling limit"; [436,437,449,450]) or even lower [451,452]. The fraction of low-mass halos that host UFDs and the scatter in the stellar mass-halo mass relation for these systems are also being studied in order to precisely characterize the properties of halos near the galaxy formation threshold [453][454][455][456].…”
Section: Ultra-faint Galaxiesmentioning
confidence: 99%
“…In parallel, semi-analytic and empirical galaxy-halo connection models have been combined with observations to infer ultra-faints' halo properties; in these models, the number of observable ultra-faints suggests that these systems occupy halos with masses down to ∼ 10 8 M (near the "atomic cooling limit"; [436,437,449,450]) or even lower [451,452]. The fraction of low-mass halos that host UFDs and the scatter in the stellar mass-halo mass relation for these systems are also being studied in order to precisely characterize the properties of halos near the galaxy formation threshold [453][454][455][456].…”
Section: Ultra-faint Galaxiesmentioning
confidence: 99%
“…This profile is fully specified by two parameters; e.g., a virial mass, 𝑀 200 , and concentration, 𝑐 = 𝑟 200 /𝑟 𝑠 , or, alternatively, by a maximum circular velocity, 𝑉 max , and the radius at which it is reached, 𝑟 max . Cosmological hydrodynamical simulations, such as the APOSTLE suite of Local Group simulations (Sawala et al 2016;Fattahi et al 2016), have shown that 𝑉 max correlates strongly with galaxy stellar mass, 𝑀 ★ (see also Santos-Santos et al 2021, for a recent compilation). We adopt a stellar mass for Crater II of 𝑀 ★ = 2.56 × 10 5 M , computed from the absolute magnitude of Torrealba et al (2016) and assuming 𝑀 ★ /𝐿 𝑉 = 1.6, typical of dwarf galaxies in the Local Group (Woo et al 2008).…”
Section: Dark Matter Componentmentioning
confidence: 99%
“…The dimensionless quantity M T /M * characterizes the history of star formation in the galaxy, as well as its present dynamic status. In recent years, many publications have appeared in which the magnitude of M T /M * is modeled depending on the luminosity or mass of the galaxy (Moster et al 2013;Sales et al 2013;Wechsler & Tinker 2018;Santos-Santos et al 2021). As shown by theoretical calculations and observational results, the minimum ratio M T /M * occurs for galaxies of the Milky Way type with M * /M e ∼ 11 dex, increasing both toward more massive galaxies and toward dwarf systems (Kourkchi & Tully 2017;Lapi et al 2018;Posti & Fall 2021).…”
Section: Introductionmentioning
confidence: 99%